An Exploration of Space and Time Metaphorical Expressions in Chinese and Italian - Stefania Profita (Journal of Linguistics and Communication Studies, 2024)
The research constitutes an initial examination of metaphorical expressions associated with temporal and spatial concepts in both the Chinese and Italian languages. Recognizing the profound influence of metaphor on cognitive constructs and linguistic representation, the study adopts a comparative analytical approach to uncover the metaphorical dimensions inherent in expressions related to time and space within these distinct linguistic frameworks. Through the examination of lexical and syntactic elements in both languages, the research aims to elucidate the subtle nuances and cultural variations that characterize the metaphorical richness of temporal and spatial discourse. By comparing Chinese and Italian linguistic structures, the study seeks to reveal commonalities and divergences in the metaphorical strategies used to express concepts related to space and time in these two languages. This comparative exploration not only contributes to a deeper understanding of the metaphorical nature embedded in Chinese and Italian discourse but also sheds light on the cultural and cognitive dimensions that shape these linguistic expressions. The findings of the study serve as a foundational exploration, paving the way for future in-depth investigations into the intricate interplay between language, metaphor, and cognition within the realms of temporal and spatial concepts in both the Chinese and Italian linguistic contexts.